SAPAAN GELAR KEAGAMAAN PADA MASYARAKAT MADURA JEMBER: KAJIAN SOSIOLINGUISTIK DENGAN PENDEKATAN SOSIAL BUDAYA - Amilia*, Fitri (Universitas Muhammadiyah Jember, 2016)
Jemberese are multicultural society for they have three different languages and cultures occupied in their interactions. This multicultural circumstance has caused the contact on the language and culture. One of the evidences can be seen from how the âMadura Jemberâ(MMJ) greets others using their religious titles. This is very interesting to be studied further for it is followed by âspecificâ a verbal and non-verbal attitudes which have not found in other greetings. This greeting and its verbal and non-verbal attitudes which followed were the reflections of a language, community and the cultural blueprints of Jemberese. The results of the study reveal that there are two systems in greetings using religious title; first is genetic or kinship and second is greeting for efforts and motivation. The genetic or kinship includes kiaÃ© [kiaÃ©], gus [gUs] or lora [lÆra], ning [nIÅ], dan nyai [Ã±ai]. Greeting for efforts and motivation includes haji, makkaÃ¨ [ma?kaÃ©], BhindhÃ¢rÃ¢Â [bhindhÃ¢rÃ¢], dan ustad. The use of genetic or kinship greeting show high social status in MMJ; it is attributed with a polite way of greeting, polite and respectful manners, obedient and conformity. In the greeting for efforts or motivation polite way of greeting is also attributed, but with a little lower degree of politeness. The exceptional of this greeting in âhajiâ is that there is a change in name on the person who owns the title.Key words: greetings, religious title